THE INFLUENCE OF BRAND IMAGE, PRICE, AND STORE ATMOSPHERE ON REPURCHASE INTENTION OF CAN NGOPI GADING SERPONG CONSUMERS - Kenneth, Kristopher; Hapsari, Ajeng Andriani (International Humanities and Applied Science Journal, 2025)
This study was conducted with the aim of analyzing the influence of brand image, price, and store atmosphere on consumers' repurchase intention at Can Ngopi Gading Serpong. The approach used in this research is a quantitative approach with purposive sampling technique. The sample consisted of 116 consumers who have previously visited Can Ngopi, and the data was collected through a questionnaire survey via Google Forms. The data analysis technique employed was Partial Least Squares (PLS) using SmartPLS 3.0 software. The results of this study indicate that the variables Brand Image (X1) and Price (X2) have a positive and significant effect on Repurchase Intention (Y). However, the variable Store Atmosphere (X3) has no significant effect on Repurchase Intention (Y).